Perception of Teachers on the Use of ChatGPT in Instructional Delivery and Assessment - Leovigildo Lito Mallillin (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The study aims to investigate the perception of teachers on the usage of ChatGPT in instructional delivery and assessment. Mixed methods are employed in the research design as a result of Focus Group Discussion in answering the extent of teachers’ perception in the usage of ChatGPT in instructional delivery and assessment. Results show that the extent of teachers’ perception in the usage of ChatGPT in instructional delivery and assessment provides supplementary aid that is paramount to quality of teaching and pedagogical decisions in providing support, perspective, and necessary context in the instructional delivery assessment, show that general attitude toward ChatGPT in Education perceives benefits for the tasks in providing better ideas to summarize complex topics and quick explanation to enhance teaching and learning, show that the perceptions on instructional delivery enhances support for the teaching tasks and efficiency to generate lessons for better ideas, customizes content alignment based on the needs of students, and refine explanations, show that perceptions on assessment supports for the assistance of ChatGPT in creating rubrics and practice items to diversify help and evaluation of student performance, and show that key themes in teachers’ perceptions provides perceived benefits for time saving in drafting and planning teaching materials to customize differentiation for the instructional delivery assessment based on the diverse needs of students.